2020
DOI: 10.1093/jb/mvaa119
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA_0092516 regulates chondrocyte proliferation and apoptosis in osteoarthritis through the miR-337-3p/PTEN axis

Abstract: The dysregulation of circular RNAs (circRNAs) has been identified in various human diseases. Here, we probed into the potential mechanism of circRNA_0092516 in osteoarthritis (OA). The expression of circRNA_0092516 was tested by quantitative real-time PCR. MTT, flow cytometry, and Western blot were applied to confirm the functions of circRNA_0092516 in vitro. Besides, RNA pull-down and dual-luciferase reporter gene experiments were applied to probe into the mechanism. circRNA_0092516 was raised in the tissues … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Several studies suggested that circRNAs play an important role in the development of OA [ 4 , 5 ]. Huang et al showed that circRNA_0092516 impairs proliferation and promotes apoptosis in IL-1β-stimulated chondrocytes by regulating the miR-337-3p/PTEN axis [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies suggested that circRNAs play an important role in the development of OA [ 4 , 5 ]. Huang et al showed that circRNA_0092516 impairs proliferation and promotes apoptosis in IL-1β-stimulated chondrocytes by regulating the miR-337-3p/PTEN axis [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that circRNAs play an important role in the development of OA [ 4 , 5 ]. Huang et al showed that circRNA_0092516 impairs proliferation and promotes apoptosis in IL-1β-stimulated chondrocytes by regulating the miR-337-3p/PTEN axis [ 4 ]. Zhu et al reported that silencing of circGCN1L1 (hsa_circ_0000448) alleviates the symptoms of OA by regulating miR-330-3p and the TNF-α gene in synoviocytes [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circular RNAs (circRNAs) are a class of noncoding RNAs produced by dorsal splicing of precursor mRNAs and are widely expressed in mammals with highly conserved, stable, and tissue-specific patterns [ 16 ]. Because circRNAs are highly expressed, structurally stable, and possess a large number of miRNA binding sites, they may be a “biological sponge”' for enriching miRNAs [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the ethanol-induced myocardial injury, SIRT1 is able to mediate phosphatase and tensin homolog (PTEN), thus affecting mitochondrial apoptosis [ 9 ]. Chondrocyte proliferation and apoptosis are influenced by the miR-337-3p/PTEN axis with altered status in OA [ 10 ]. PTEN also regulates epidermal growth factor receptor (EGFR) ubiquitination, and inactivation of PTEN specifically increases EGFR activity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%